Pax3 and Hippo Signaling Coordinate Melanocyte Gene Expression in Neural Crest - Lauren J. Manderfield; Kurt A. Engleka; Haig Aghajanian; Mudit Gupta; Steven Yang; Li Li; Julie E. Baggs; John B. Hogenesch; Eric N. Olson; Jonathan A. Epstein (Cell Reports, 2014)
Summary: Loss of Pax3, a developmentally regulated transcription factor expressed in premigratory neural crest, results in severe developmental defects and embryonic lethality. Although Pax3 mutations produce profound phenotypes, the intrinsic transcriptional activation exhibited by Pax3 is surprisingly modest. We postulated the existence of transcriptional coactivators that function with Pax3 to mediate developmental functions. A high-throughput screen identified the Hippo effector proteins Taz and Yap65 as Pax3 coactivators. Synergistic coactivation of target genes by Pax3-Taz/Yap65 requires DNA binding by Pax3, is Tead independent, and is regulated by Hippo kinases Mst1 and Lats2. In vivo, Pax3 and Yap65 colocalize in the nucleus of neural crest progenitors in the dorsal neural tube. Neural crest deletion of Taz and Yap65 results in embryo-lethal neural crest defects and decreased expression of the Pax3 target gene, Mitf. These results suggest that Pax3 activity is regulated by the Hippo pathway and that Pax factors are Hippo effectors. : Hippo signaling is a conserved kinase cascade that mediates transcription through a Yap65/Taz-Tead complex and governs organ size. Manderfield et al. have identified Yap65 and Taz as coactivators of Pax factors and established neural crest as a novel site of Hippo signaling. The Pax3-Yap65/Taz complex is regulated by upstream Hippo kinases and is Tead independent. Deletion of Yap65 and Taz in neural crest generated differentiation defects in specific neural crest derivatives.